DEVELOPMENT OF CONSTRUCT 3-BASED EDUCATION GAME STEM PEDIA SIAR FOR LEARNING SCIENCE MATERIAL OF WATER CYCLE IN GRADE V ELEMENTARY SCHOOL - Fauziyah, Eva; Rochmah, Eliya; Labudasari, Erna (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
The rapid development of technology in the 21st century has an impact on the field of education. One of them requires teachers to continue to innovate and create learning media. In the learning process, there are still many teachers who have not used digital media or are integrated with technology, thus affecting students' understanding of the concept of science in the water cycle material. This research purpose is to develop science educational game learning media, namely STEM Pedia SiAr based on Construct 3. This research uses a method of Research and development model from Borg and Gall. The results of this research are: 1) This research produces education game learning media products for grade V elementary school that focus on science material of water cycle using Construct 3 software; 2) The results of the media expert test get an average score of 94.90% with very decent criteria. While the results of the material expert test get an average score of 98.07% with very feasible criteria.